Scientific Reasoning in Science Education: From Global Measures to Fine-Grained Descriptions of Students’ Competencies - Krell, Moritz; Vorholzer, Andreas; Nehring, Andreas (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book is a reprint of the Special Issue "Scientific Reasoning in Science Education: From Global Measures to Fine-Grained Descriptions of Students' Competencies" published in the journal Education Sciences. It compiles all manuscripts of the special issue.